1986
DOI: 10.1042/cs0710621
|View full text |Cite
|
Sign up to set email alerts
|

Vasopressin and catecholamine secretion during apomorphine-induced nausea mediate acute changes in haemostatic function in man

Abstract: Seven male volunteers were given apomorphine (14-20 micrograms/kg) subcutaneously on a total of ten occasions. Nausea was experienced on six occasions and on four occasions there was no effect. Venous samples were taken before injection, at peak nausea and 20 min later for assay of factor VIII coagulant activity (FVIIIC), von Willebrand factor antigen (vWFAg), the ristocetin cofactor (FVIIIRiCof), euglobulin clot lysis time (ECLT), fibrinopeptide A (FPA), FPA generation time, activated partial thromboplastin t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
1

Year Published

1987
1987
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 0 publications
2
10
1
Order By: Relevance
“…Apomorphine-induced nausea caused a marked rise in plasma AVP in normal subjects similar to that seen in other studies (Rowe et al, 1979;Baylis et al, 198,l;Sorensen & Hammer, 1985;Grant et al, 1986). We have previously demonstrated that the immunoreactive AVP released in response to this stimulus is chromatographically identical to synthetic peptide and is bioactive (Nussey et al, 1986b).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Apomorphine-induced nausea caused a marked rise in plasma AVP in normal subjects similar to that seen in other studies (Rowe et al, 1979;Baylis et al, 198,l;Sorensen & Hammer, 1985;Grant et al, 1986). We have previously demonstrated that the immunoreactive AVP released in response to this stimulus is chromatographically identical to synthetic peptide and is bioactive (Nussey et al, 1986b).…”
Section: Discussionsupporting
confidence: 85%
“…Early studies in humans and dogs showed that nausea and vomiting produced in response to several stimuli (motion sickness, ethanol, copper sulphate, apomorphine) caused a marked anti-diuresis (Andersson & Larsson, 1954;Taylor et al, 1957;Coutinho, 1969). Later studies using AVP radioimmunoassays confirmed the massive rise in plasma AVP in response to motion sickness (Eversmann et al, 1978), the dopamine (D2 receptor) agonist apomorphine (Rowe et al, 1979;Baylis et al, 1981;Sorensen & Hammer, 1985;Grant et al, 1986) and chemotherapeutic agents (Fisher et al, 1982). The role of this release of AVP in nausea and vomiting is unknown although in man therapeutic i.v.…”
Section: Introductionmentioning
confidence: 99%
“…Only 1 dysmenorrheic woman had markedly increased plasma concentrations of vasopressin. These might have resulted from nausea (this woman being the only one to report nausea during the experiments), as nausea is known to be a strong stimulator of vasopressin release [24]. Not only were we unable to demonstrate an effect of Atosiban on menstrual pain in dysmenorrheic women, but we also found that Atosiban had no effect on intrauterine pressure, uterine artery PI or plasma concentrations of 15-ketodihydro-PGF 2· .…”
Section: Discussioncontrasting
confidence: 32%
“…Many treatments that produce nausea and vomiting, such as apomorphine, chemotherapy, motion, and cholecystokinin, also increase plasma vasopressin to varying extents including to levels exceeding maximal levels for anti-diuresis (Rowe et al, 1979;Fisher et al, 1982;Grant et al, 1986;Feldman et al, 1988;Miaskiewicz et al, 1989;Edwards et al, 1989;Koch et al, 1990b). Plasma vasopressin levels appear to increase slightly before or at the onset of nausea (Miaskiewicz et al, 1989;Koch et al, 1990b).…”
Section: Neurohypophyseal Hormonal Secretions and Gastric Dysrhythmiamentioning
confidence: 99%